(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Stroke is the leading cause of disability and a major public health issue in worldwide. Outcomes of ischemic stroke are directly related to the location and types of strokes. Aim: To compare outcome of anterior and posterior circulation ischemic stroke at six months. Methodology: A prospective cohort study was carried out in the department of Neurology, Dhaka Medical College hospital from January 2022 to February 2023. A total 200 subjects were included in this study based on inclusion and exclusion criteria Neurological state of the patient was assessed on the 1st day of hospitalization by National institute of Health Stroke Scale (NIHSS) and functional status of the patient were assessed on discharge, 1 month, 3 months and 6 months after onset of stroke by Modified Rankin scale (mRS). A mRS of 3 to 6 was considered as poor outcome and mRS of 0-2 as good outcome. Results: In this study, mRS was d”2 in 59%, 66%, 74% and 79% after anterior circulation stroke and mRS was d”2 in 65%, 70%, 76% and 77% after posterior circulation stroke respectively at discharge, 1month, 3 months and 6 months. It was found improved progressively at different follow-up periods in both groups. So, no significant (p>0.05) difference was observed in mRS score of both groups. In present study, mortality at 6 months after stroke was 7% and 17% in ACS and PCS groups respectively. Statistically significant (p=0.029) difference was observed in mortality of both groups at 6 months follow-up. Binary analysis showed that age (OR:1.48, 95% CI: 1.170 to 1.864), male gender (OR:0.44; 95%CI: 0.188 to 1.032), duration of stroke (OR: 1.69; 95% CI: 1.208 to 2.361), initial NIHSS score (OR:1.35; 95%CI: 1.098 to 1.653) and artery-to-artery embolic occlusion (ATO) (OR:1.36; 95%CI: 1.196 to 1.548) in anterior circulation stroke and duration of stroke (OR: 1.89; 95% CI: 1.185 to 3.013), initial NIHSS score (OR:0.34; 95%CI: 0.255 to 0.470), artery-to-artery embolic occlusion (ATO) (OR:1.72; 95% CI: 1.120 to 2.634), cardioembolic occlusion (CAO) (OR:0.57; 95% CI: 0.448 to 0.722) and intracranial arterial steno-occlusion (ICASO) (OR:1.36; 95% CI: 1.007 to 1.840) in posterior circulation stroke were independently associated (p<0.05) with favorable 6-months mRS scores. Conclusion: It can be concluded that the proportions of favorable outcomes at 1 month, 3 months and 6 months follow-up period were similar between the two groups, whereas 6 months mortality was higher in the posterior circulation stroke group than the anterior circulation stroke group.